Water and Indigenous Peoples in Latin America: An Overview of Academic Publications - Valverde Morales, Marcelo (2026)
This work is structured around three main lines of inquiry. The first offers a general description of the normative framework concerning cultural human rights, the human rights of Indigenous peoples, and the human right to water—particularly as established in Latin America, within both the international and inter-American human rights systems. The second line of research consists of a bibliographic review of works published since 2000 that address water and Indigenous peoples in Latin America, contributing to the conceptual development of the aforementioned rights. Finally, the third line proposes an analysis, from the perspective of critical human rights theory, of the potential of the research findings.